2018
DOI: 10.21061/jte.v29i2.a.3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Holographic, 3D-Printed, and Computer-Generated Models: Implications for Engineering Technology Students’ Spatial Visualization Ability

Abstract: A number of studies indicate that the use of holographic displays can influence spatial visualization ability; however, research provides inconsistent results. Considering this, a quasi-experimental study was conducted to identify the existence of statistically significant effects on sectional view drawing ability due to the impacts of holographic displays. In particular, the study compared the use of three different types of displays: 3D printed model, computer generated model, and holographic model to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Unfortunately, the relevant literature is extremely limited and most studies that examined the use of pyramid holograms either evaluated the learning outcomes using pre-posttests (e.g., Loh & Shaharuddin, 2019b) or compared the results with conventional tools (for example, printed material; e.g., Cerezo et al, 2019;Roslan & Ahmad, 2017). One study comparing pyramid holograms and conventional videos concluded that holograms had more positive results in terms of knowledge acquisition (Orcos & Magreñán, 2018) while another found no differences, but it was related to the development of design skills (Katsioloudis & Jones, 2018). Therefore, both because of the limited literature and contradictory results of past research, it is not easy to interpret the study's results regarding learning; this leaves room only for assumptions, as discussed in the coming paragraphs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the relevant literature is extremely limited and most studies that examined the use of pyramid holograms either evaluated the learning outcomes using pre-posttests (e.g., Loh & Shaharuddin, 2019b) or compared the results with conventional tools (for example, printed material; e.g., Cerezo et al, 2019;Roslan & Ahmad, 2017). One study comparing pyramid holograms and conventional videos concluded that holograms had more positive results in terms of knowledge acquisition (Orcos & Magreñán, 2018) while another found no differences, but it was related to the development of design skills (Katsioloudis & Jones, 2018). Therefore, both because of the limited literature and contradictory results of past research, it is not easy to interpret the study's results regarding learning; this leaves room only for assumptions, as discussed in the coming paragraphs.…”
Section: Discussionmentioning
confidence: 99%
“…This has a positive effect on the visualization skills of the trainees (Roslan & Ahmad, 2017). Furthermore, it seems that this kind of holograms are also suitable for subjects related to spatial information (Katsioloudis & Jones, 2018). They also seem to reduce the cognitive load (Loh & Shaharuddin, 2019a) and, at the same time, increase the learners' interest in what is presented to them (Lee et al, 2016).…”
Section: The Hologram-like Pyramid Projectormentioning
confidence: 93%
See 1 more Smart Citation
“…Pearson and Dubé (2022) identified multiple studies showing promising effects for (mathematics-) education, such as increased mental rotations skills and understanding through visualization. (Huang & Lin, 2017;Katsioloudis & Jones, 2015) However, these effects are only possible with significant effort of the teacher. (Ford & Minshall, 2019) While this opens possibilities for students, teachers, and educators, the negatives of 3D(M)P are considerable: long print times for even small objects, a large technical overhead, and a high need for instructor support and training indicate that the complexity of 3D(M)P may not be fully advantageous and integration of 3DMP into lessons faces difficulties.…”
Section: Tim Läufer Matthias Ludwigmentioning
confidence: 99%
“…Digital hologram was described as records created by the three-dimensional interference of laser light waves (Jampala & Shivnani, 2014). The concept of digital hologram is also defined as mediators that can bring 3-D images of certain objects to different settings and ensure the continuity of the image even in the absence of these objects (Katsioloudis & Jones, 2018).…”
Section: Introductionmentioning
confidence: 99%